Impact of Krakatau Festival on the Tourism growth in Lampung province, Indonesia - Basri, Hasan; Evadianti, Yuli; Hernawan, Wawan (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study aims to determine the effectiveness of Krakatau Festival initiated by the Lampung provincial tourism office to promote tourism in the province. It is a qualitative research using case study approaches. Data collection is carried out by conducting interviews and reviewing documents. Research response were determined by purposive sampling techniques by selecting people considered to have interests in the festival. Results showed that the festival had an impact on the number of tourist visits, hospitality growth and ocupancy rates. It can be concluded that Krakatau Festival is effective in encouraging the growth of tourism industry in Lampung Province, Indonesia.